Anatomical and radiologic approach to tracheal diverticula - Selma Caliskan; Emre Can Celebioglu; Sinem Akkasoglu; Ibrahim Tanzer Sancak (Medicine Science, 2019)
Tracheal diverticula (TD) are benign conditions characterized by single or multiple outpouchings from the tracheal wall. Different series which demonstrate tracheal diverticula on autopsy series, fiber optic bronchoscope examinations, and CT images are found in the literature. Treatment options for TD are surgical resection, endoscopic cauterization with laser or electrocoagulation and conservative management. Surgery is the treatment choice for young patients, while conservative treatment is recommended for elderly patients. We performed a retrospective study on 2271 patients who underwent thoracic CT examination for different reasons. Presence, number, anatomical location, level, diameter, cystic component, and accompanying variations were assessed and recorded. A total of 2271 patients were evaluated in the present study. 73 patients (38 females, 35 males) with TD were detected. The prevalence of TD was found to be 3.2%. It was found more frequently in women (52.1%) than in men (47.9%). The mean diameter of the diverticula was 4.5 mm (range 1-15 mm) in females and 5mm (1-14) in males. There was no difference between gender groups according diameter median values (p=0.811). TD was solitary in 71 (97.2%) patients and doubled (2.7%) in two patients. In conclusion our data showed a female predilection of prevalence, but no statistically significant difference between gender and other parameters (diameter, side, and level) was indicated. Patients with paratracheal air cysts that have no connection with the tracheal lumen were also analyzed in this study, and cystic groups diameter values were found to be higher than the non-cystic group. This difference was found to be statistically significant. [Med-Science 2019; 8(4.000): 796-9]